A Shift-Share Analysis of Cancer Incidence Across Northern Europe. (3rd April 2019) - Sanchez, Michael U.; Leslie, Timothy F.
Abstract: There is perhaps no disease in the modern era as geographically ubiquitous as cancer. Despite the high rates of the disease, particularly in developed countries, there is some geographic variability in the types of cancer that spread in certain parts of the world, with some cancers being more prevalent in specific regions. We introduce a new application of shift-share analysis to break down cancer incidence. The application of shift-share analysis to cancer research is a new approach to understanding the geographic distribution of cancer that decomposes cancer incidence into three components: the national growth effect, the cancer mix effect, and the local share effect. Regions of Denmark, Scotland, southern Sweden, and Wales were found to be central to several high-incidence clusters, including melanoma and bladder cancer. The application of gender-specific shift-share analysis to cancer incidence yielded noteworthy results in the average increase of cancer between men (1.5 percent) and women (6.3 percent) across the entire study area as well as cancer-specific elements. Our results suggest further research for cancer health surveillance.